Genre-related temporary collocations in english discourse - E V Terekhova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2009)
The paper discusses genre-related temporary collocations (TC). It also provides genre definition, analyzes different genre-related TC which are used in TV speeches, diplomatic texts, and English media texts. TC implementing in genre-related texts, preferential reinterpretation criteria which characterize terminology formation, their interpretation, and their translation from English into Russian is considered.